1995
DOI: 10.1021/bi00035a004
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of an ATP-Dependent Carboxylase, Dethiobiotin Synthetase, Based on Crystallographic Studies of Complexes with Substrates and a Reaction Intermediate

Abstract: The crystal structures of six complexes of homodimeric Escherichia coli dethiobiotin synthetase with a variety of substrates, substrate analogs, and products have been determined to high resolution. These include (1) the binary complex of dethiobiotin synthetase and the N7-carbamate of 7,8-diaminononanoic acid, (2) the binary complex of enzyme and the alternate substrate, 3-(1-aminoethyl)-nonanedioic acid, (3) the binary complex of enzyme with the product ADP, (4) the quaternary complex of enzyme, ADP, the N7-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
79
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(81 citation statements)
references
References 22 publications
2
79
0
Order By: Relevance
“…The reaction mechanism has been proposed to involve three discrete steps, which are (1) the formation of N7-carbamate, (2) the formation of the carbamic-phosphoric acid anhydride, and (3) the closure of the ureido ring with the release of inorganic phosphate [14]. The amino acid residues required for binding the DAPA substrate and subsequent catalysis have been well characterized, with X-ray crystal structures available for the enzymes from Escherichia coli, M. tuberculosis, Helicobacter pylori, and Francisella tularensis [15], [16], [17] and [18]. However, the molecular details of NTP binding are less well defined, especially for M. tuberculosis DTBS (MtDTBS) where there is currently no crystal structure of the enzyme in complex with NTP.…”
Section: Introductionmentioning
confidence: 99%
“…The reaction mechanism has been proposed to involve three discrete steps, which are (1) the formation of N7-carbamate, (2) the formation of the carbamic-phosphoric acid anhydride, and (3) the closure of the ureido ring with the release of inorganic phosphate [14]. The amino acid residues required for binding the DAPA substrate and subsequent catalysis have been well characterized, with X-ray crystal structures available for the enzymes from Escherichia coli, M. tuberculosis, Helicobacter pylori, and Francisella tularensis [15], [16], [17] and [18]. However, the molecular details of NTP binding are less well defined, especially for M. tuberculosis DTBS (MtDTBS) where there is currently no crystal structure of the enzyme in complex with NTP.…”
Section: Introductionmentioning
confidence: 99%
“…In most bacteria, the enzyme uses S-adenosyl-L-Met (AdoMet) as amino group donor, an unusual feature among aminotransferases (Izumi et al, 1975;Breen et al, 2003;Mann and Ploux, 2006). DTBS is a homodimeric enzyme that catalyzes the formation of the ureido ring of dethiobiotin (DTB) from DAPA and CO 2 in the presence of ATP and divalent metal ions ( Figure 1A) (Alexeev et al, 1995;Huang et al, 1995). In Arabidopsis, genetic studies revealed that DAPA-AT (BIO1; BioA ortholog) and DTBS (BIO3; BioD ortholog) are encoded by adjacent genes, defining a single genetic locus, and are expressed in both single and chimeric BIO3-BIO1 transcripts through alternative splicing events (Muralla et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The enzymes involved in the conversion of pimeloyl coenzyme A (CoA) to biotin have been isolated from both of these bacterial species and characterized (2,14,16,23,29,42). The analogous pairs of enzymes from the two species are similar, although some of the components involved in the last step in biotin synthesis remain to be elucidated (6,15,25,26,37,46).…”
mentioning
confidence: 99%